Human trends and humanization of engineering education in Russia; 2nd Global congress on engineering educanion - Pokholkov Y. P. Yuri Petrovich (2000, 2000)
This paper presents the principal features of a contemporary Russian technical university: human trends, humanisation, fundamntalisation, and professionalism in education. The problems of the content and methods of the application of the educational experience in human trends and humanisation of engineering education in Russia have also been canvassed